Pengaruh Nilai-Nilai Etika Terhadap Pencapaian Kinerja Bisnis (Studi Empiris Pelaku Ekonomi) - Damanhuri; Misbah, T. Lembong; Hasyim, Syarifuddin; Mistiar, Wolly (Journal of Law and Economics, 2024)
The research aims to analyze the implementation of business ethics values in Small and Medium Enterprises (SMEs) in Banda Aceh City. Through a quantitative approach with survey method, data collection involved 150 SME owners as respondents selected through stratified random sampling technique. Data were collected using structured questionnaires and analyzed using multiple regression analysis. The results show that the implementation of business ethics values has a positive and significant effect on SME performance, with honesty in transactions as the most dominant factor (41.2%). There are significant differences in the implementation of business ethics values based on business sectors, where the service sector shows a higher level of implementation. The research findings benefit the development of business ethics for SMEs in developing countries